Being Through Doing: The Self-Immolation of an Asylum Seeker in Switzerland - Womersley, Gail; Kloetzer, Laure (Frontiers in Psychiatry, 2018)
In April 2016, Armin, an asylum seeker in a village of Switzerland, set himself alight in the public square of the town, one of a few cases reported across Europe. He performed the act following a denied request for asylum and was saved by bystanders. We present the results of two qualitative interviews conducted with Armin, his translator and his roommate following the incident. The act is theorized through the lens of a dialogical analysis focusing on the concept of social recognition. The notion of trauma is considered as a key mediating mechanism, theorized as creating ruptures in time, memory, language, and social connections to an Other. We conclude this communicative act to represent both “being-toward-death” and a relational striving towards life; a “destruction as the cause of coming into being.”